Meningkatkan Penampilan Broiler dengan Pemacu Pertumbuhan Alami - A A Candra; K Magfiroh (Politeknik Negeri Lampung, 2019)
The study aims to determine the effect of the addition of probiotics, prebiotics and eubiotics in broilers on the appearance of broiler production. The material used was 100 broilers, which were kept from Day Old Chicks until the age of 4 weeks and distributed in 4 groups, namely probiotics, prebiotics and eubiotics. The research method was experimental compiled based on a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments tested were as follows: the control group (without any additions), probiotics, prebiotics and eubiotics. The variables observed in this study were feed consumption; weight gain (PBB); feed conversion; carcass weight and mortality. The data obtained were analyzed using analysis of variance and if there were differences between treatments. The results showed that the addition of probiotics, prebiotics and eubiotics increased weight gain, increased consumption and was able to suppress the value of feed conversion.Keywords: Broiler, Appearanc, Growth Boosters